2011
DOI: 10.1007/s00701-011-1187-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrode dysfunctions in patients with deep brain stimulation: a clinical retrospective study

Abstract: Technical dysfunctions of stimulation electrodes or extension leads are rare but important sources of unsatisfying DBS efficacy. In the majority of cases DBS programming or reprogramming allows avoiding surgical revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Therapy impedance represents the resistance to current flow for the specific stimulation parameters being used to treat the patient. Electrode impedance is measured at standardized stimulation parameters and is monitored clinically because abnormal values may indicate electrode dysfunction such as a short or open circuit [11]. Impedance varies significantly between patients and has a substantial effect on the extent of tissue activation, as it affects the amount of current being delivered to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Therapy impedance represents the resistance to current flow for the specific stimulation parameters being used to treat the patient. Electrode impedance is measured at standardized stimulation parameters and is monitored clinically because abnormal values may indicate electrode dysfunction such as a short or open circuit [11]. Impedance varies significantly between patients and has a substantial effect on the extent of tissue activation, as it affects the amount of current being delivered to the brain.…”
Section: Introductionmentioning
confidence: 99%
“… showed that 20% of patients reported a worsening of clinical conditions although there was no evidence of technical problems; it was suggested that the decrease in symptom control was related to an altered current flow at the active contacts, with a consequent change in the volume of activated tissue. In our series the percentage of reported worsening was lower than that reported in the previous studies , and the rate of electrode dysfunction of 5%, corresponding to one case, was lower than that reported in the Allert et al . study .…”
Section: Discussionmentioning
confidence: 99%
“…Placing the connector high on the head is proposed . Clinical retrospective studies have reported that lead fracture is rare with this technique . This procedure might increase the incidence of infection or skin erosion if the connector is too bulky ; however, this can be avoided by lowering the profile of the connector and/or using specific surgical techniques, such as drilling a trough or avoiding putting the connector directly under the suture line .…”
Section: Discussionmentioning
confidence: 99%